Fiscal Policy, Monetary Policy and Price Volatility: Evidence from an Emerging Economy - Tung, Le Thanh (Organizations and Markets in Emerging Economies, 2021)
Vietnam is an Asian emerging country, which now is ranked in the group of the fastest-gro- wing economies worldwide. However, this economy has faced galloping inflation in recent years. So the Vietnamese experience is a valuable reference for the policymakers in the developing world in order to successfully control price volatility. Our study applies the Vector autoregressive method, the Johansen cointegration test, and the Granger causality test to examine the impact of fiscal and monetary policy on price volatility in Vietnam with a quarterly data sample collected over the period from 2004 to 2018. The study results confirm the existence of a long-term cointegration relationship between these policies and price volatility in Vietnam. Besides, the variance decomposition and impulse response function also show that the impact of these policies on inflation is clear, however, the fiscal policy more strongly affects inflation than the monetary policy. Finally, the Granger causality test also indicates one-way causality relationships from the government expenditure as well as the exchange rate to price volatility in the study period.
Keywords: price volatility; inflation; fiscal policy; monetary policy; emerging economy; Vietnam